2007
DOI: 10.1016/j.rmed.2007.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perception of asthma severity

Abstract: FDMA identified variables patients used to determine PS. It highlighted a discrepancy between patients' and doctors' perceptions of asthma severity, suggesting that assessment of asthma severity should consider both patients' and doctors' perceptions of the disease and includes an AQLQ measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Our data suggest that people find it difficult to express asthma severity and control to their healthcare teams, and indeed it is known that patients often underestimate their asthma severity [22,23]. Such discrepancies between perception and objective asthma severity could have drastic consequences in the management of the disease.…”
Section: Discussionmentioning
confidence: 83%
“…Our data suggest that people find it difficult to express asthma severity and control to their healthcare teams, and indeed it is known that patients often underestimate their asthma severity [22,23]. Such discrepancies between perception and objective asthma severity could have drastic consequences in the management of the disease.…”
Section: Discussionmentioning
confidence: 83%
“…It was shown that patient perceived asthma severity is substantially different from doctor rated asthma severity, with lower levels of asthma severity reported by patients, although a different scale of asthma severity was used in that study [36]. Meanwhile, it was reported that underestimating asthma severity can result in inadequate management of the disease and more frequent morbidity [37][38][39], which can potentially explain our findings that women with the same level of asthma control but with higher perceived diseases severity had a higher asthma-specific quality of life.…”
Section: Discussionmentioning
confidence: 87%
“…Usually, it is related to the use of fuzzy rules as a representation of the model, for instance fuzzy decision trees [27] or fuzzy association rules [28]. For instance, in the Medical domain, the proposal of a fuzzy representation for numerical variables representing patients can greatly increase the understandability of the links between the description of patients and their classes [29,30].…”
Section: Interpretability Of the Modelmentioning
confidence: 99%